2019
DOI: 10.3390/jmse7120433
|View full text |Cite
|
Sign up to set email alerts
|

Intratidal and Subtidal Circulation in a Tropical Estuary during Wet Season: The Maroni, French Guiana

Abstract: Observations of water level, current velocity, river discharge, wind and salinity were collected in the Maroni estuary, on the border of French Guiana and Suriname during the wet season of 2018 to explore subtidal circulation patterns. Measurements are complimented by the application of analytical models with an aim to diagnose forcing mechanisms responsible for producing subtidal flows during the day of data collection and to extrapolate these findings to other time periods with variable wind and river forcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The estuary shows a converging plan shape, with tidal range amplification at about 8 km from the mouth [15]. Ross et al [16] identified an ebb channel at the west bank of the estuary (Suriname) and a flood channel at the east bank (French Guiana) ( Figure 1c). A mud bank started impinging on the mouth of the Maroni in 2011 ( Figure 1d) [36], and it is still migrating across the estuary.…”
Section: Maroni River and Estuarymentioning
confidence: 96%
See 3 more Smart Citations
“…The estuary shows a converging plan shape, with tidal range amplification at about 8 km from the mouth [15]. Ross et al [16] identified an ebb channel at the west bank of the estuary (Suriname) and a flood channel at the east bank (French Guiana) ( Figure 1c). A mud bank started impinging on the mouth of the Maroni in 2011 ( Figure 1d) [36], and it is still migrating across the estuary.…”
Section: Maroni River and Estuarymentioning
confidence: 96%
“…During ebb tides, the ETM is well developed (Figure 6b,f) and is located in the area between the downstream islands (KP 20and KP 0). High values of SPM are observed at the west bank of the estuary, which has been identified as the ebb channel [16], especially for 2018, when the length of the ETM was considerably longer than that of 2014 (Figure 6b,f). This is consistent with the results of Jolivet et al [36]: the dominant direction of transport of sediments from this river is westwards along the Suriname coast.…”
Section: Spm and Variability Of Etm Extension Due To External Conditionsmentioning
confidence: 98%
See 2 more Smart Citations
“…monitored in these river mouths (Orseau et al 2017;Sottolichio et al 2018;Ross et al 2019), modelled (Do Anh et al, 2020, and analysed through remote sensing (Abascal Zorrilla et al 2020).…”
Section: Methodsmentioning
confidence: 99%